Disseminated cryptococcal infection initially presenting as cryptococcal cellulitis in an HIV-negative patient on long-term steroids. Issue 1 (28th November 2018) - Kerr, Colm; Stack, William A; Sadlier, Corinna; Jackson, Arthur
Abstract : Cryptococcosis is an invasive fungal infection caused by encapsulated yeasts of the Cryptococcus species. Inoculation usually occurs by inhalation through the respiratory tract, where it can then spread haematogenously to various sites, such as the central nervous system or the skin, in susceptible patients. We present the case of a 68-year-old male patient on long-term steroids who presented with a right upper limb cellulitis not responding to antibiotics. This was subsequently diagnosed as cryptococcal cellulitis on an urgent skin biopsy. Wound swabs and blood cultures, which were initially negative, were repeated and confirmed the presence of disseminated cryptococcal disease. The patient's neighbours kept racing pigeons and this was hypothesised as a potential source of infection.